Pemberdayaan Masyarakat melalui Program Kampung Madani dalam Upaya Peningkatan Kualitas Hidup di Kecamatan Simokerto Kota Surabaya - Azulfa, Farah Diba; Dwiyanti, Olifvia; Habibah, Jessica Wildani; Widiyarini, Tri Tiya; Fachira, Aisyah Arifah; Hardjati, Susi (IAI Nasional Laa Roiba Bogor, 2024)
The city of Surabaya is one of several cities that has a level of poverty which is a serious problem that is being faced and overcome. The Surabaya City Government is implementing a number of initiatives aimed at reducing poverty, including initiatives that meet the three main needs of underprivileged communities: housing, health services, and education. Madani villages were formed as an effort to mobilize residents and community leaders to improve economic conditions. The aim of this research is to determine the implementation of community empowerment through the Madani Village Program as an effort to improve living standards in Simokerto District, Surabaya City. This research uses a qualitative method with a case study approach. Documentation, interviews and observations were used to collect data. The results of this research show that with the ongoing empowerment program, it has been found that the community can be said to be independent and able to develop its business. This is proven by the stage of enthusiastic community participation, the stage of selecting locations that already have businesses, socialization which is able to provide understanding to the community about Kampung Madani, the empowerment process of forming KUBE and collaboration with CSR, then the stage of self-reliance by the community being able to produce products.